Evaluasi dan Perbaikan Antarmuka Aplikasi Lembar Kerja Anggaran Investasi PT. PLN (Persero) Area Malang Menggunakan Metode Cognitive Walkthrough dan Heuristic Evaluation - Danu Firmansyah Hidayatullah; Retno Indah Rokhmawati; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang Area LKAI (Investment Budget Worksheet) application is a web based application that can be used by employees in PT. PLN (Persero) Malang Area planning sector to recapitulate data from field surveys related network reinforcement and suppression of distribution programs. Based on the results of interviews conducted LKAI application, problems were found that there were no instructions on how to fill data on the location description modal box, there was no detailed info on the user being logged in, and the size of the job blank is small. The evaluation was conducted to find usability problems using the Cognitive Walkthrough and Heuristic Evaluation methods. In this evaluation involving 3 evaluator subject matter and 3 evaluator usability expert. The evaluation using Cognitive Walkthrough method found 205 usability problems which were then normalized to 22 problems, while 64% of all problems were also found in Heuristic Evaluations. While Heuristic Evaluation method found 20 usability problems, while usability heuristic with the highest number of problems was H-5 (Error prevention) with 5 findings or 25% of the all problems finding. The evaluation results, 30 prototype interface improvements based on the 10 guideline of usability heuristic principles. Then validation on the prototype using the system usability scale obtained a score of 80.83 with the acceptability level depending on the acceptable category, grade scale was in grade B, adjective ranking depends on the excellent category and percentile rank in grade A.